Behavioral Pharmacology From Basic to Clinical Research - Francisco Rodríguez-Landa, Juan; Cueto-Escobedo, Jonathan (IntechOpen, 2020)
Behavioral pharmacology studies the biological bases of behavior and the pharmacological effects of natural or synthetic drugs through behavioral analysis, with the identification of substances that could contribute to improvement of the quality of life for humans. Through behavioral pharmacology, it is possible to generate knowledge about pharmacological bases that influence the normal or altered behavior from a multidisciplinary point of view, and which includes diverse areas of science. The purpose of this book "Behavioral Pharmacology- From Basic to Clinical Research" is to show some of the advances in the identification of pharmacological properties of natural and synthetic molecules that may be used in the development of pharmacological therapies destined for the treatment of illness and disorders that affect the wellness of humans.